An Economical Modification Method for MIL-101 to Capture Radioiodine Gaseous: Adsorption Properties and Enhancement Mechanism - Peng Wang; Bing-Bing Qi; Ao-Tian Gu; Kai-Wei Chen; Chun-Hui Gong; Yang Yi (Adsorption Science & Technology)
Radioactive iodine is one of the inevitable by-products of nuclear energy application. However, it is a great threat to public health and the adsorbent needs to be adopted for removing the radioactive iodine. The iodine adsorbent needs to have some advantages, such as simple preparation method, low cost, high absorption capacity, and recyclable utilization. In order to meet the above requirements, the etched material of institute Lavoisier 101 (MIL-101) was prepared to absorb the gaseous iodine. After the MIL-101 is etched, the iodine adsorption performance has been greatly improved. The iodine adsorption experiment of etched MIL-101 with different etching time (1 h, 3 h, 4 h, and 6 h) was completed, the results show that the optimal etching time is 4 hours and the capture capacity of the etched MIL-101 is 371 wt%, which is about 22% higher than that of original MIL-101. The experiment results of XRD, FT-IR, and XPS prove that the components and structure of etched MIL-101 are accordable with those of MIL-101. The surface roughness is introduced in this work. The pore roughness is also an important factor to the adsorption capacity, and the related research also supports this conclusion. Furthermore, after iodine is absorbed, etched MIL-101 can be treated by ethanol for iodine release, and the etched MIL-101 has satisfied recyclability within three cycles. Compared with MIL-101, etched MIL-101 not only had good reversible adsorption of iodine but also can adsorb low-concentration iodine. The etched MIL-101 has a broad application prospect in nuclear emergency response and radiation detection.